Kant and the systematicity of nature. The regulative use of reason in Kant's Critique of Pure Reason - Spagnesi, Lorenzo (The University of Edinburgh, 2021)
What makes scientific knowledge possible? The philosopher Immanuel Kant in his magnum opus, the Critique of Pure Reason, had a fascinating and puzzling answer to this question. Scientific knowledge, for Kant, is made possible by the faculty of reason and its demand for systematic unity (or, ‘systematicity’). In other words, cognition about empirical objects can aspire to be scientific only if it is rationally embedded within or transformed into a system. But how can such system form once we take into account the perspectival nature of knowledge, i.e., its being situated in individual human cognitive faculties? My PhD thesis has a two-pronged objective: (i.) to reconstruct the complexity of the notion of systematicity in Kant’s Critique of Pure Reason; and (ii.) to defend its plausibility in contemporary debates on the unity or plurality of scientific knowledge. As far as (i.) is concerned, Kant’s position is far from being clearly understood in the literature. Despite a renewed interest in Kant’s notion of systematicity in recent decades, existing contributions fail to offer a satisfactory account of it. The aim of my thesis is to provide a unified reading of reason’s systematicity as an essential feature of Kant’s analysis of the sources of cognition. In particular, I defend a novel account of theoretical reason the aims to support the following claims: (a.) systematicity is grounded in a legitimate use of reason’s ideas as prescriptive rules for empirical investigation; (b.) it is necessary to make empirical cognition possible and generate scientific hypotheses; and (c.) it gives us fundamental insights into Kant’s ‘empirical realism’ and his understanding of the role of metaphysics in science. With regard to (ii.), I show that Kant’s account of theoretical reason has much more to offer than generally acknowledged. In particular, I present it as providing a reconciling solution to the conflict between unity and pluralism in contemporary philosophy of science. Drawing inspiration from Kant’s ‘perspectivism,’ I argue that unity and pluralism are to be thought as mutually inclusive principles of scientific knowledge.
Keywords: Kant; Systematicity; Scientific Knowledge; Reason; Ideas